Peran Kelompok Tani dalam Meningkatkan Produksi Pertanian: (Studi pada Kelompok Tani Bersaudara Desa Oelbubuk Kecamatan Mollo Tengah Kabupaten Timor Tengah Selatan) - Claudya Maria Benadikti Tan; Nursalam Nursalam; Delila A. Nahak Seran; Rouwland A. Benyamin (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of the Bersaudara Farmers Group in increasing agricultural production in Oelbubuk Village, Mollo Tengah District, Timor Tengah Selatan Regency, and to identify the inhibiting factors. The research employed a qualitative descriptive approach. Informants were selected using purposive sampling, involving the village head, agricultural extension officer, group management, members, and community representatives. Data were collected through interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the Bersaudara Farmers Group has functioned as a learning class through training, counseling, mentoring activities, and the adoption of innovations such as cultivator use and banana-leaf pot trays, which improved efficiency and reduced production costs. As a cooperation forum, the group established partnerships with government agencies and other institutions that contributed to increased production and land expansion, although some collaborations were temporary. As a production unit, the group provided agricultural facilities and facilitated marketing to inter-regional markets; however, collective product storage remains suboptimal and overproduction occurs during peak harvest periods. Inhibiting factors include weak institutional management, low member participation, limited capital, internal conflicts, limited water access, price instability, and climate and pest disturbances. It is concluded that although the group’s role has been implemented, it is not yet optimal and requires institutional strengthening and better production planning to achieve sustainable agricultural production improvement.